2017
DOI: 10.1155/2017/3851262
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Pattern of Microgliosis in the Olfactory Bulb of Neurodegenerative Proteinopathies

Abstract: The olfactory bulb (OB) shows early neuropathological hallmarks in numerous neurodegenerative diseases, for example, in Alzheimer's disease (AD) and Parkinson's disease (PD). The glomerular and granular cell layer of the OB is characterized by preserved cellular plasticity in the adult brain. In turn, alterations of this cellular plasticity are related to neuroinflammation such as microglia activation, implicated in the pathogenesis of AD and PD, as well as frontotemporal lobe degeneration (FTLD). To determine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 69 publications
5
23
0
Order By: Relevance
“…Histopathological findings in the olfactory bulb of EAE-affected mice revealed that infiltration of inflammatory cells and subsequent microgliosis were evident; this has also been shown in the olfactory bulb of human MS patients [15], suggesting that olfactory deficits in both human MS and the animal model of EAE are associated with neuroinflammation in the olfactory bulb, a central region of olfaction. Alternatively, reduced migration of progenitor cells to the olfactory bulb has been suggested as a cause of olfactory deficit in EAE-affected mice [26].…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Histopathological findings in the olfactory bulb of EAE-affected mice revealed that infiltration of inflammatory cells and subsequent microgliosis were evident; this has also been shown in the olfactory bulb of human MS patients [15], suggesting that olfactory deficits in both human MS and the animal model of EAE are associated with neuroinflammation in the olfactory bulb, a central region of olfaction. Alternatively, reduced migration of progenitor cells to the olfactory bulb has been suggested as a cause of olfactory deficit in EAE-affected mice [26].…”
Section: Discussionmentioning
confidence: 74%
“…Olfactory dysfunction occurs as a result of axonal degeneration in primary progressive MS patients, and CNS inflammation in relapsing-remitting MS patients [13]. In neurodegenerative diseases, microglial activation in the olfactory bulb is thought to be a consequence of CNS inflammation [1516], which also partially interrupts neural transmission [17]. Microglial activation has been also shown in the olfactory bulb of Niemann-Pick disease type C1 mice [1819].…”
Section: Introductionmentioning
confidence: 99%
“…Olfactory dysfunction can be caused by olfactory bulb microglia activation, which can be induced by Alzheimer's, Parkinson's, and Niemann-Pick disease type C (10,21). In a previous study by our group, rats after MCAO had microglia and macrophage activation in the ischemic side of the brain (22).…”
Section: Discussionmentioning
confidence: 85%
“…Actually, microgliosis are representative pathological changes that develop during neuroin ammation of central nervous system (CNS) [2]. A close link between microglial hyperplasia of olfactory bulb and olfactory dysfunction has been reported in the patients and animal models of the neuroimmunological disorders, including experimental autoimmune encephalomyelitis (EAE), Alzheimer's disease (AD) and Parkinson's disease (PD) and so on [3][4][5]. Furthermore, recent studies have shown that airway allergen exposure directly induces neuroin ammation [6,7], such as increased Th2-type cytokines and nNOS in the olfactory bulb of airway in ammation animal models [8,9].…”
Section: Introductionmentioning
confidence: 99%